2017
DOI: 10.1177/1559827617745479
|View full text |Cite
|
Sign up to set email alerts
|

Advocating for Behavior Change With Education

Abstract: Education is ubiquitous with clinical care. However, not all education supports behavioral change. Education is a broad term that encompasses the process of obtaining general knowledge, personal awareness, and skills training. Although not sufficient, education is a necessary component for behavior change. This article outlines the role of education in behavior change and offers practical suggestions for how clinicians can provide education to their patients to help them change behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
3
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(153 citation statements)
references
References 24 publications
6
125
3
19
Order By: Relevance
“…This technique requires the identification and use of community groups (external and internal) that most members of the community frequently orient themselves with and to use them to modify emptying perceptions that could create the attitudes and intentions to undertake the desired emptying behaviour (Tom et al, 1987); V. Evaluating and addressing the feedback of target populations is a technique designed to make agreed solutions more responsive and meet the goals of the perception change programme so as to cause a change in behaviour (Arlinghaus and Johnston, 2017). Feedback techniques whether generic, targeted and/or personalised should provide useful solutions to address all challenges that militated against the adoption of the desired behaviour (Arlinghaus and Johnston, 2017); and VI. Information and education provides knowledge, facts, and skills that are needed to strengthen the perceptions that create the right attitudes and intentions of households to adopt desired emptying behaviour.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…This technique requires the identification and use of community groups (external and internal) that most members of the community frequently orient themselves with and to use them to modify emptying perceptions that could create the attitudes and intentions to undertake the desired emptying behaviour (Tom et al, 1987); V. Evaluating and addressing the feedback of target populations is a technique designed to make agreed solutions more responsive and meet the goals of the perception change programme so as to cause a change in behaviour (Arlinghaus and Johnston, 2017). Feedback techniques whether generic, targeted and/or personalised should provide useful solutions to address all challenges that militated against the adoption of the desired behaviour (Arlinghaus and Johnston, 2017); and VI. Information and education provides knowledge, facts, and skills that are needed to strengthen the perceptions that create the right attitudes and intentions of households to adopt desired emptying behaviour.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…The goal of the group education in this study was to ensure that adolescent athletes maintained healthy eating habits and positive body image to achieve a healthy lifestyle and high athletic performance. However, as education alone cannot guarantee positive behavioral changes, it is necessary to encourage adolescent athletes to change their dietary behavior by improving their personal awareness and skills through customized counseling 34 . Although most adolescent athletes understand that optimal nutrition is essential in training programs 35 , the vast majority of them do not link nutritional knowledge with practical food choice behaviors 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Health educational interventions are not only effective in increasing knowledge and awareness, but several studies have also demonstrated change in disease-specific measures and outcomes following educational interventions (Ghisi et al, 2014). While often critical in informing change, general knowledge alone is not enough to drive behavior change if the education does not build relevant skills and enhance self-efficacy to engage in the targeted health behavior (Arlinghaus & Johnston, 2018). In the current study, participants were educated on "what to do" but also on "how to do it" to achieve the desired results.…”
Section: Lifestyle Changesmentioning
confidence: 99%